Early transcriptional events linked to induction of diapause revealed by RNAseq in larvae of drosophilid fly, Chymomyza costata - Poupardin, Rodolphe; Schöttner, Konrad; Korbelová, Jaroslava; Provazník, Jan; Doležel, David; Pavlinic, Dinko; Beneš, Vladimír; Koštál, Vladimír (BMC genomics, 2015)
BACKGROUND: Diapause is a developmental alternative to direct ontogeny in many invertebrates. Its primary adaptive meaning is to secure survival over unfavourable seasons in a state of developmental arrest usually accompanied by metabolic suppression and enhanced tolerance to environmental stressors. During photoperiodically triggered diapause of insects, the ontogeny is centrally turned off under hormonal control, the molecular details of this transition being poorly understood. Using RNAseq technology, we characterized transcription profiles associated with photoperiodic diapause induction in the larvae of the drosophilid fly Chymomyza costata with the goal of identifying candidate genes and processes linked to upstream regulatory events that eventually lead to a complex phenotypic change. RESULTS: Short day photoperiod triggering diapause was associated to inhibition of 20-hydroxy ecdysone (20-HE) signalling during the photoperiod-sensitive stage of C. costata larval development. The mRNA levels of several key genes involved in 20-HE biosynthesis, perception, and signalling were significantly downregulated under short days. Hormonal change was translated into downregulation of a series of other transcripts with broad influence on gene expression, protein translation, alternative histone marking by methylation and alternative splicing. These changes probably resulted in blockade of direct development and deep restructuring of metabolic pathways indicated by differential expression of genes involved in cell cycle regulation, metabolism, detoxification, redox balance, protection against oxidative stress, cuticle formation and synthesis of larval storage proteins. This highly complex alteration of gene transcription was expressed already during first extended night, within the first four hours after the change of the photoperiodic signal from long days to short days. We validated our RNAseq differential gene expression results in an independent qRT-PCR experiment involving wild-type (photoperiodic) and NPD-mutant (non-photoperiodic) strains of C. costata. CONCLUSIONS: Our study revealed several strong candidate genes for follow-up functional studies. Candidate genes code for upstream regulators of a complex change of gene expression, which leads to phenotypic switch from direct ontogeny to larval diapause.
Keywords: sekvenční analýza RNA; transkriptom; Cluster Analysis; Drosophilidae; vývojová regulace genové exprese; Transcription, Genetic; Gene Expression Regulation, Developmental; Transcriptome; shluková analýza; stanovení celkové genové exprese; reprodukovatelnost výsledků; Reproducibility of Results; Gene Expression Profiling; genetická transkripce; larva; Animals; zvířata; Sequence Analysis, RNA; Larva